Evaluating the role of quantitative pupillometry in chronic subdural hematoma: A pilot study - Lukas Klein; Christopher Beynon; Daniel Kühlwein; Sandro M. Krieg; Alexander Younsi; Pavlina Lenga (Brain and Spine)
Introduction: As the incidence of chronic subdural hematoma (cSDH) increases with an aging population, identifying noninvasive methods for early detection and monitoring is crucial. Brain atrophy in older adults creates additional intracranial reserve, allowing large hematomas to accumulate without significantly elevating intracranial pressure (ICP). We investigated whether quantitative pupillometry (QP) could detect subtle pressure changes or neurological compromise in these patients. Methods: This prospective study included 26 elderly cSDH patients between 65 and 97 years of age undergoing standard cranial computed tomography (cCT) and surgical burr-hole hematoma evacuation at our institution. Pupillometry assessments were conducted prospectively using the automated NPi 200® Pupillometer and the Neurological Pupil Index (NPi) was measured pre- and post-operatively. Clinical and radiological parameters including the initial Glasgow Coma Scale (GSC) score, hematoma volume, residual cavity area (RCA), and the Evans index were obtained and all parameters were statistically compared. In addition, correlation analyses were performed (p < 0.05 was considered significant). Results: The median hematoma volume was 132.5 ml (IQR 82.2 ml), with a median RCA of 4.4 mm (IQR 6.2 mm), and a median Evans index of 0.5 (IQR 0.1). Preoperatively, the mean NPI was 4.6 (SD 0.9) in the right eye and 4.5 (SD 0.5) in the left eye. No statistically significant differences were observed when directly comparing NPI, GCS, hematoma volume, RCA, Evans index, and the presence of motor deficits to one another. However, RCA showed significant positive correlations with age (rs = 0.3; p = 0.026), Evans index (rs = 0.5; p = 0.003), and hematoma volume (rs = 0.14; p = 0.043). There was also a trend toward a negative correlation between RCA and GCS (rs = −0.7; p = 0.053), as well as between hematoma volume and left-eye NPI (rs = −0.3; p = 0.058). Conclusions: In this cohort of older cSDH patients, pupillometry did not reveal any abnormal responses, suggesting that the intracranial reserve created by brain atrophy may prevent the development of elevated ICP—despite large hematoma volumes. Research is warranted to identify additional biomarkers or strategies to improve early cSDH-detection and management.